HUBUNGAN POWER OTOT TUNGKAI DENGAN LARI CEPAT (SPRINT) PADA ATLET ATLETIK PUTRI LANCANG KUNING CLUB - Undayah, Dewi; Ramadi, Ramadi; Wijayanti, Ni Putu Nita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Based on writer observation result on the athlete athletic daughter lancang kuning club fonded symptons of in the sport run fast ( sprint ) including is at the moment run speed peddle foot down and your feet to contact the soil is not maximum, the speed of the step and long step is still slow and less maximum. This research aims to know the correlation is significant the relationship power of leg muscle with run fast ( sprint ) on the athlete athletic doughter lancang kuning club. The population in this research is athlete athletic doughter lancang kuning club that numbered 7 people. as for the sampling technique used is sampling total. Therefore sample of this research is athletec daughter who number 7 people. Test instrument explosive power leg musele by using a standing broad and speed with a hundred yards. Data obtained in analysis by using a technique of correlation moment product. Based on the rejults of research and processing data by using research statistics procedure, so it is can conclude that to the correlation between X variable with Y variable obtained score r = 0,388 so rxy < rtabel that is ( 0,388 < 0,811 ), so Ha rejected, in other words there is no correlation that significant between power of leg muscle with run fast ( sprint ) on the athlete athletic daughter lancing kuning club.Key Word : Explosive Power Leg Muscle, Run Fast ( Sprint )